2004
DOI: 10.1108/09564230410564948
|View full text |Cite
|
Sign up to set email alerts
|

New service development: learning from and with customers

Abstract: New service development relies on the complex task of understanding and anticipating latent customer needs. To facilitate proactive learning about the customer, recent findings stress customer involvement in the development process and observations of customers in real action. This paper draws on theory from market and learning orientation in conjunction with a service‐centered model, and reviews the literature on customer involvement in innovation. A field experiment was conducted in Sweden with end‐user mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
287
0
25

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(321 citation statements)
references
References 71 publications
(116 reference statements)
9
287
0
25
Order By: Relevance
“…In this process, the suppliers and customers become inseparable and learning from the interaction is important (Matthing et al, 2004). In addition, as these events form complex and volatile paths over time, it is important to take a longitudinal perspective to the development of value-in-use (Ballantyne, 2004;Macdonald et al, 2011).…”
Section: Assessing Value-in-usementioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the suppliers and customers become inseparable and learning from the interaction is important (Matthing et al, 2004). In addition, as these events form complex and volatile paths over time, it is important to take a longitudinal perspective to the development of value-in-use (Ballantyne, 2004;Macdonald et al, 2011).…”
Section: Assessing Value-in-usementioning
confidence: 99%
“…Therefore, the aim of suppliers is to acquire invitations to take part in the customers' own internal usage processes and to understand the value-in-use for the customers to be able to engage in value co-creation more extensively (Ballantyne & Varey, 2006;Grönroos, 2006;Payne et al, 2008). Consequently, relation-specific knowledge and a longitudinal perspective on the development of value-in-use were identified as relevant aspects of the issue (Ballantyne, 2004;Macdonald et al, 2011;Matthing et al, 2004).…”
Section: Integrating the Concepts Of Value-in-use And Social Platformmentioning
confidence: 99%
“…Kristensson et al (2008) have argued that there is a lack of a firm theoretical foundation on which to base an understanding of the practical processes and mechanisms which are required for success during co-creation. While the necessary elements and interconnections, as well as the benefits of co-creation, have been highlighted in the literature (Kristensson et al, 2004;Matthing et al, 2004, Prahalad & Ramaswamy, 2004and Ballantyne & Varey, 2006), this study set out to explore potential tools that would be required in order for business to practically enable cocreation with consumers. The research found that the how of co-creation also remains elusive in the context of developing solutions to sustainable consumption in the grocery retail sector.…”
Section: The Role Of Consumer Influencementioning
confidence: 99%
“…Hsieh and Chen (2005) showed that new product development can be enhanced by interacting with users, and capitalising on user-knowledge management competencies, supporting the assertion by Bennet and Gabriel (1999) of the importance of customer knowledge for an organisation. Matthing, Sanden and Edvardsson (2004) suggest that the value of customer involvement in new service development resides in the opportunity to facilitate proactive learning about the customer, and to understand and anticipate latent customer needs.…”
Section: An Introduction To Value Co-creationmentioning
confidence: 99%
“…This differs from NPD, which is typically centrally initiated, more structured, and driven by new technology or the new use of existing technologies. A key to successful service innovation is to understand the customers' businesses and needs, including involving customers in the development process, from idea generation (Matthing et al 2004) to pilot testing and continuous feedback during usage (Oliveira and von Hippel 2011). By fostering customer relationships, companies become more knowledgeable about their operational and strategic needs.…”
mentioning
confidence: 99%